Heritage Productions - Music Variety Show (African Knowledges and the History Publication since the 1970s)
Music show including live performance of song by Kpleketen Man of Africa with band and dancers, and music video by Larry Zanga.
Keywords: Music; Music videos; Live Music; Contemporary Music